A Review of Clostridium difficile Infection at the University Hospital of the West Indies, Jamaica - Clare-Pascoe, N (West Indian Med J, 2015)
OBJECTIVES: This study examined the frequency of Clostridium difficile infection (CDI) among hospital admission and diarrhoeal stool samples over a six-year period. METHODS: A review of all suspected cases of C difficile positive patients from 2007 to 2012 at the University Hospital of the West Indies (UHWI), Jamaica, was performed. Clostridium difficile infection was confirmed by clinical features and a positive enzyme-linked immunosorbent assay (ELISA) stool test for Clostridium Toxins A and B. The demographics, clinical features, risk factors, treatment and outcomes were also collated. RESULTS: There were 56 patients reviewed. The most commonly affected age group was 40–59 years of age. The proportion of CDI cases per total stool samples increased from 0.5% in 2007 to 5.9% in 2010 then fell to 2.2% in 2011 but increased again to 4.3% in 2012. The proportion of cases per total UHWI admissions also increased from 0.12 cases per 1000 admissions in 2007 to 1.16 in 2010 and 1.36 in 2012 (p < 0.001). Most CDI cases were nosocomial (76% males, 48.6% females). Co-morbidities included hypertension and end-stage renal disease. Ceftazidime was the most common antibiotic associated with the development of CDI. Resolution occurred in 62.5% of patients. Duration of hospital stay was longer in males than females (≥ 21 versus < 7 days) and males had more adverse outcomes, with death in 23.8% versus 11.4%. CONCLUSION: There has been an increase in the frequency of CDI at UHWI with a greater than expected frequency of community acquired CDI. Increased awareness is needed of the increasing risk for CDI and measures must be taken to prevent the disease, especially in hospitalized patients.